Subjective quality of life and social work Social Widerspiegelung as a basis - Autrata, Otger; Scheu, Bringfriede (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2023)
Social Widerspiegelung is a central area of human life, however, it has been little researched for the theorization of social work. Otger Autrata and Bringfriede Scheu present the foundations of social Widerspiegelung and establish the essential connection between social Widerspiegelung and subjective quality of life. This makes an important contribution to the development of social work theory: The basic research on social Widerspiegelung is linked to the tasks of social work in discipline and profession. The authors Otger Autrata is head of the research institute RISS in Feldkirchen in Carinthia. Bringfriede Scheu holds a professorship for the theory of social work in the Bachelor's and Master's degree programme in social work at the Carinthian University of Applied Sciences. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation bythe service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
Starting point -- Reflection: an approach -- Social Widerspiegelung in humans: Fundamentals -- Social Widerspiegelung in Humans: Social Widerspiegelung in Humans: Perspective -- Social Widerspiegelung in Humans: Perspective.
Keywords: Social service -- Research; Social service; Social Work Research; Theory and Method in Social Work; Social Work Consulting